Consumer behavior models on online purchase of horticultural commodities - Miftah Himmatul; Widyasari R.A. Hangesti Emi; Putri Raden Roro Chieka; Mibarokah Syaima Lailatul; Masithoh Siti; Pramarta Ikhsan Qodri (E3S Web of Conferences)
An increase followed the increasing trend of online purchases in online sales platform providers. Increased fraud cases and the ease of use of features on online sales platforms impact consumer behavior in online purchasing decisions for agricultural commodities. This study aims to determine the characteristics of consumers and the stages of consumer purchasing decisions, analyze the influence of trust, ease of use, and lifestyle factors on purchasing decisions, and develop models of consumer purchasing decisions for horticultural commodities online. The research was conducted using a survey method with a purposive sampling method. Data were analyzed descriptively and quantitatively so that a regression model was composed. The model used is multiple linear regression. The results show that the trust variable (X1), ease of use (X2), and lifestyle (X3) have a real influence on purchasing decisions (Y). This study supports the model presented by previous researchers. The practical recommendation from this research is for e-commerce business actors to always maintain their reputation by guaranteeing the trustworthiness of their transactions so that horticultural consumers are willing to make repeat purchase transactions and recommend them to other consumers. Business actors should display application features that are easy to use, practical, and fast. The model shown can be used to develop competitive strategies for improving services to online consumers.